Local anesthesia in surgery of urinary incontinence in women - M Yu Gvozdev; I A Reva; N V Tupikina; D Yu Pushkar (IP Berlin A.V., 2014)
Introduction. To date, the methods of surgical treatment of stress urinary incontinence minimally invasive techniques are gaining more and more popularity. Application of mini-loops allows the surgeon to fully control the installation process of loops under the middle part of the urethra, as well as to perform the operation with minimal surgical aggression, under local anesthesia.Goals and objectives. The study was focused on assessing the efficacy and safety of the operation to install Ophira suburethral mini-loop under local anesthesia.Materials and methods. The treatment experience of 28 patients suffering from stress urinary incontinence was analyzed. The average age was55,5 years. Preoperative evaluation included a survey in the gynecological chair with carrying out functional tests («the cough» test, test with straining), urethrocystoscopy, ultrasound and complex urodynamic examination. All patients were induced with Ophira suburethral mini-loops under local anesthesia. Results. Intraoperative and serious early postoperative complications were recorded. Duration of operational benefits was around 18,4 min. In 1 month after surgery no signs of obstructive voiding were shown in patients. The other complications such as wound infection, pain symptom, hinge erosion or dispareunia were absent as well.Conclusions. Ophira mini-loop has proven efficacy in the treatment of urinary incontinence and has several advantages over other synthetic loops. Lo-wer cost of consumables for anesthesia, no need for anesthesia team and expensive equipment, and as a result, less patients staying in hospitals: all those factors can significantly reduce costs.